ZnO nanowires for photoelectric converter applications - Kidalov, Valerii; Кідалов, Валерій Віталійович; Кидалов, Валерий Витальевич; Sosnytska, Natalia; Сосницька, Наталя Леонідівна; Сосницкая, Наталья Леонидовна; Дяденчук, Альона Федорівна; Дяденчук, Алена Федоровна; Diadenchuk, Alona; Oleksenko, Roman; Олексенко, Роман Іванович; Олексенко, Роман Иванович (My University, 2021)
This work is focused on the creation and study of photosensitive structures based on zinc oxide nanofibers, which are promising for solar energy. Zinc oxide nanowires were obtained on the porous zinc selenide surface. The porous substrate was obtained by electrochemical etching of a low-resistance n-ZnSe plate (110) with a polished surface. Nanowires were deposited by radical-beam epitaxy. The annealing temperature was varied from 400° C to 500° C. The oxygen radical flux was 1.5∙1017 cm-2s-1. The process duration was 50 minutes. According to the scanning electron microscopy results, the nanowires length reaches 10 μm, the nanowires diameter is ~1 μm. The predominant X-ray diffraction reflex at 2θ=34.44° indicates the polycrystalline nature of the manufactured ZnO coatings with a wurtzite-type hexagonal lattice. The study of nanowires ZnO luminescence at room temperature contains an ultraviolet peak around 385 nm. This peak is related to the zinc oxide edge luminescence. Based on the fabricated structure, the design of the photoconverter was developed. The upper contact of the fabricated photoelectric converter was created by vacuum thermal sputtering of aluminum through a mask. The deposition was carried out at a substrate temperature of 200° C. Ohmic contacts were made using conductive silver paste. The reverse ohmic contact was formed by applying Al paste to the entire reverse side of the surface. The upper layer of the structure is an array of ZnO nanowires. The active base layer is ZnSe. The light volt-ampere characteristics of the obtained structure were measured in the AM 1.5 illumination mode. No-load voltage Uxx, short-circuit current Isc and the fill factor of the current-voltage characteristic FF of the solar element were measured. The efficiency of the manufactured photoconverter was 13.7 %.
Keywords: photosensitive structures; electrochemical etching; radical-beam epitaxy; nanowires; solar energy; photoconverter